Biodegradasi Limbah Padat Organik secara anaerob: Proses semi kontinu - Sriwuryandari, Lies; Sembiring, Tarzan (Teknologi Indonesia, 2009)
On the minimizing of organic solid waste coming to open dumping area, the municipal organic waste was used as substrate for anaerobic degradation and methane generation. Experiment either in the semi continuous bioreactor or in serum vials showed that the rate of organic substance conversion is low. The degradation rate is between 3550 % of organic material feed into bioreactor where pH is in optimum condition for methane generation. The overall limiting step of organic material biodegradation is the hydrolysis of organic fiber into soluble organic substance.